The lexical-syntactic representation of number - Nickels, L.; Biedermann, Britta-Andrea; Fieder, N.; Schiller, N. (Routledge, 2015)
Number is an important aspect of lexical syntax. While there has been substantial research devoted to number agreement at the level of the sentence, relatively less attention has been paid to the representation of number at the level of individual lexical items. In this paper, we propose a representational framework for the lexical syntax of number in spoken word production that we believe can account for much of the data regarding number in noun and noun phrase production. This framework considers the representation of regular and irregular nouns, and more unusual cases such as pluralia tantum (e.g. scissors), zero plurals (e.g. sheep) and mass nouns (e.g. garlic). We not only address bare noun production but also the production of determiner + noun phrases. While focusing on examples from English, we extend the framework to include languages with grammatical gender such as German.